2016
DOI: 10.2967/jnumed.116.178228
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Radioligand Therapy of Metastatic Castrate-Resistant Prostate Cancer with 177Lu-PSMA-617

Abstract: Radioligand therapy (RLT) with 177 Lu-PSMA-617 (PSMA is prostatespecific membrane antigen) is a novel targeted therapy for metastatic prostate cancer. In this study, we evaluated the effect of different pretherapeutic parameters on the therapeutic response measured by prostate-specific antigen (PSA) 2 mo after RLT. Methods: RLT was performed in 40 hormone-refractory patients with distant metastases and progressive disease (mean age, 71.4 y). 68 Ga-PSMA-11 PET/CT was performed in all patients 1-2 wk before RLT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
4
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 28 publications
(36 reference statements)
10
108
4
16
Order By: Relevance
“…Cutoffs of PSMA intensity on 68 Ga‐PSMA below which 177 Lu PSMA therapy may not be effective have not yet been established. A recent study of 40 patients identified platelet level and the need for pain relief as the most significant predictor of poor response to 177 LU‐PSMA, likely reflective of the burden of metastatic bone disease 26. This same study did not find that intensity of PSMA activity on 68 Ga‐PSMA staging PET/CT was predictive of response, but this is likely because intense PSMA activity on 68 Ga‐PSMA imaging was one of the inclusion criteria for receiving 177 Lu PSMA therapy initially 26.…”
Section: Predictors Of Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Cutoffs of PSMA intensity on 68 Ga‐PSMA below which 177 Lu PSMA therapy may not be effective have not yet been established. A recent study of 40 patients identified platelet level and the need for pain relief as the most significant predictor of poor response to 177 LU‐PSMA, likely reflective of the burden of metastatic bone disease 26. This same study did not find that intensity of PSMA activity on 68 Ga‐PSMA staging PET/CT was predictive of response, but this is likely because intense PSMA activity on 68 Ga‐PSMA imaging was one of the inclusion criteria for receiving 177 Lu PSMA therapy initially 26.…”
Section: Predictors Of Responsementioning
confidence: 99%
“…A recent study of 40 patients identified platelet level and the need for pain relief as the most significant predictor of poor response to 177 LU‐PSMA, likely reflective of the burden of metastatic bone disease 26. This same study did not find that intensity of PSMA activity on 68 Ga‐PSMA staging PET/CT was predictive of response, but this is likely because intense PSMA activity on 68 Ga‐PSMA imaging was one of the inclusion criteria for receiving 177 Lu PSMA therapy initially 26. Other studies have commented that bone metastases appear to respond less well than visceral or lymph nodal disease to treatment with Lu PSMA 3…”
Section: Predictors Of Responsementioning
confidence: 99%
“…Nuclear targeted therapies play an essential role, especially in patients with advanced neuroendocrine tumors, such as gastroenteropancreatic (GEP) tumors, bronchopulmonary neuroendocrine tumors, pheochromocytoma, and neuroblastoma 10,11,20,2227. Furthermore, there are positive results with radioligand therapies in metastatic PC and metastatic melanoma 8,13,19,28,29…”
Section: Introduction: Goals Of Theranostics In Nuclear Medicinementioning
confidence: 99%
“…In fact, nearly 70% of patients have benefited from this therapy 13,28,85–90. Dosimetry studies have shown that the most critical organs are the kidneys, with a maximum kidney radiation dose of 0.88 Gy/GBq for [ 177 Lu]Lu-PSMA-617 and 0.93 Gy/GBq for [ 177 Lu]Lu-PSMA-I&T 91,92.…”
Section: Introduction: Goals Of Theranostics In Nuclear Medicinementioning
confidence: 99%
“…Initial clinical experience was followed by multiple relatively small single-institution studies reporting on initial clinical experience with 177 Lu-PSMA RLT (3)(4)(5)(6)(7)(8). However, these studies included a wide range of patients with varying initial and subsequent treatments, different disease stages, and variable study endpoints.…”
Section: See Page 85mentioning
confidence: 99%